2018
DOI: 10.1016/j.tranon.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Barrett's Adenocarcinoma. A First Step Towards Identifying Patients at Risk and Developing Therapeutic Paths

Abstract: BACKGROUND: Barrett's esophagus metaplasia is the key precursor lesion of esophageal adenocarcinoma. The aim of this study was to find a subset of markers that may allow the identification of patients at risk for esophageal adenocarcinoma, and to determine genes differentially expressed in esophageal squamous cell carcinoma. METHODS: Laser capture microdissection technique was applied to procure cells from defined regions. Genome-wide RNA profiling was performed on esophageal adenocarcinoma (n = 21), Barrett's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Multiple studies indicated that MMP1 participates in the progression of various cancers and is associated with an increased cancer risk[32,33]. Up-regulation of MMP1 has already been observed in EAC and BE samples[34], but has not been fully investigated. In our study, the ROC analysis found that the sensitivity, specificity, and AUC were relatively high in both datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicated that MMP1 participates in the progression of various cancers and is associated with an increased cancer risk[32,33]. Up-regulation of MMP1 has already been observed in EAC and BE samples[34], but has not been fully investigated. In our study, the ROC analysis found that the sensitivity, specificity, and AUC were relatively high in both datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The EDC, located on chromosome 1q21.3, contains clustered multigene families of genes associated with cornified envelope formation in stratified squamous epithelia, such as the S100 and the small proline-rich region (SPRR) genes 34 . Among the overlapping downregulated genes in both cell models, ANXA9 is also associated with differentiating keratinocytes 35 , and EVPL , SCEL , and KLK7 are cornified envelope genes 36 – 38 . EMP1 and SERPINB13 downregulation is associated with increased disease severity in gastric cancer ( EMP1 ) and head and neck squamous cell carcinoma (SCC) ( SERPINB13 ) 39 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…These experiments also provide mechanistic support for the notion that HOXA13 expression may offer an explanation as to why BE is prone to progression to EAC. HOXA13 mediates down-regulation of the EDC and many EDC and cornified envelope genes are progressively down-regulated in the BE to EAC cascade 36 , 41 . In BE, EAC, and esophageal SCC, loss of heterozygosity (LOH) of the EDC is common 42 44 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of activating mutations within EGFR in esophageal adenocarcinomas defines a previously unrecognized subset of gastrointestinal tumors in which EGFR signaling may play an important, biological role 42 . According to an analysis of genes strongly up-regulated in both esophageal adenocarcinoma and Barrett’s esophagus, REG4 might be of particular interest as an early marker for esophageal adenocarcinoma 43 .…”
Section: Resultsmentioning
confidence: 99%